Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Dan Kepuasan Kerja Terhadap Kinerja Pegawai (Studi Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kota Madiun) - Niko Septiawan; Ahadiati Rohmatiah; Hartirini Warnaningtyas; Retno Iswati (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
This Study aims to examine and determine the effect of partially or simultaneously transformational leadership style, motivation and job satisfaction on the performance of the employees of the Public Works and Spatial Planning Office Of Madiun City. This research is a type of the ditrisbution of questionnaires and secondary data obtained from previus research. The population in this study were employees of the Public Works and Spatial Planning Office of Madiun City, amounting to 60 respondents with the method used for this study was the saturated sampling method. the data analysis technique used multiple linier regression analysis, classical assumption test, coefficient of determination test, t test, F test using SPSS version 25.00 program. The results of the hypothetical research show that the transformational leadership style variable has a positive and significant effect on the performance of the employees of the Public Works and Spatial Planning Office of Madiun City with a significance value of 0,043. The motivation variable has no positive and significant effect on the performance of the employees of the Public Works and Spatial Planning Office of Madiun City with a significance value of 0,626. the job saticfaction variable has a positive and significan effect on the performance of the employees of the Public Works and Spatial Planning Office of Madiun City with a significance value of 0,000. The variables of transformational leadership syle, motivation and job satisfaction have a simultaneous effect on the performance of the Public Works and Spatial Planning Officers of Madiun City. Key Word : Transformational Leadership Style, Motivation, Job Saticfaction, Performance.